2022
DOI: 10.1093/jopart/muac004
|View full text |Cite
|
Sign up to set email alerts
|

Resisting or Facilitating Change? How Street-Level Managers’Situational WorkContributes to the Implementation of Public Reforms

Abstract: Managers of street-level organizations play an important role in the successful implementation of public reforms. A prevailing view within the public administration literature is that this work involves the adaptation between reforms and local contexts, where divergence is viewed as a form of resistance to change. The paper challenges this prevalent reform-centric view by introducing a situation-centric perspective and coining the concept of situational work as a significant form of managerial work during impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 56 publications
0
15
1
Order By: Relevance
“…Functionally, Klemsdal et al (2022) argue that mid-level managers act as implementers of policy, translating policies formulated at a 1 Bangladesh has a Westminster-type parliamentary democratic system comprising two tiers of government. The first tier is referred to as the 'central government' that encompasses The Executive, Cabinet, Ministries and other central government agencies such as PMO.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, Klemsdal et al (2022) argue that mid-level managers act as implementers of policy, translating policies formulated at a 1 Bangladesh has a Westminster-type parliamentary democratic system comprising two tiers of government. The first tier is referred to as the 'central government' that encompasses The Executive, Cabinet, Ministries and other central government agencies such as PMO.…”
Section: Methodsmentioning
confidence: 99%
“…Gassner and Gofen (2018, p. 551) classify these actors as heads of local-level organisations, 'who are overarchingly in charge of, and accountable for, the direct delivery of multiple policies to a local target population'. Klemsdal et al (2022), citing examples of heads of welfare agencies in municipalities, refer to them as 'middle managers' who navigate between the needs of the local population for effective service delivery and being accountable to strategic-level senior managers and policymakers. Indeed, some studies (e.g., Breit et al, 2022;Oberfield & Incantalupo, 2021) have explored this unique group of actors, but they advocate the extension of Lipsky's (1980) street-level views of discretion, rather than the reconciliation of this framework with the top-down constraints with which mid-level public managers must contend.…”
mentioning
confidence: 99%
“…The majority of research has been on organizational and state-owned enterprise (SOE) change from the managers' and decision-makers' perspectives (Yeung, 2020). Politicians and policymakers face a significant barrier in successfully implementing organizational reform; yet, little empirical research has confirmed the challenges PSUs face when implementing ownership reforms, particularly at the employee level (Klemsdal et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Successful public organizations' reform implementation is a massive issue for governments and decision-makers. Employee resistance is a crucial factor influencing organizational reform processes and sustainability, according to scholars and policy implementers (Joshi, 2005;Klemsdal et al, 2022). Numerous theories and models have been applied to explain employees' evaluations and acceptance behaviors related to new policy implementations (Schiavone, 2012;Li, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation